Effect of Nostalgia on Customer Loyalty to Brand Post-Merger/Acquisition - Ana Carolina Toledo; Evandro Luiz Lopes (BAR: Brazilian Administration Review, 2016)
The main objective of this study is to identify the effect of nostalgic feelings on consumer loyalty to the prevailing brand following the extinction of a brand in a merger/acquisition process. We also propose an explanatory model of the relationships between tests of relevant constructs. Based on a review and theoretical reflection on the constructs under study, this paper outlines a theoretical model in which attitudes in relation to both extinct and prevailing brands mediate the relationship between nostalgic feelings and customer loyalty, which was subsequently analyzed by structural equation modeling. The results showed the effect of nostalgic feelings on customers’ attitudes toward both extinct and prevailing brands and the influence of switching costs on building brand loyalty. The study contributed to the expansion of the theoretical framework on the subject of marketing by developing and validating a comprehensive model that adds to existing research, expanding the horizon of the study of the phenomenon.